Efektivitas Perma Nomor 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan dalam Menekan Angka Cerai di Pengadilan Agama - Lilik Andaryuni; Ratu Haika (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2018)
Raising statistic divorce from year to year increased, make Supreme Court take various efforts, among others make the role of mediation in the Religious Court (PERMA No. 1 Tahun 2016). This article discusses the effectiveness of mediation in the Religious Court in order to minimize statistic divorce in the Religious Court East Kalimantan.